(untitled) (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To determine the causes of first trimester vaginal bleeding using Ultrasonography. Methods: This is a hospital based cross sectional study conducted from July to December 2019. Ultrasonogram scan was done for the 200 women within 12 weeks of pregnancy with a positive pregnancy test and vaginal bleeding in in out-patient set up. Results: Majority were under 30 years of age and 45.5% diagnosed as threatened Abortion. More than half were non-viable pregnancy. Conclusions: Ultrasound examination is the essential diagnostic and confirmatory tool to diagnose early pregnancy bleeding in clinical set up. Keywords: Clinical examination, first trimester bleeding, ultrasonography.